2008
DOI: 10.1155/2008/670235
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructural Organization of Naturally Occurring Composites—Part II: Silica‐Chitin‐Based Biocomposites

Abstract: Investigations of the micro- and nanostructures and chemical composition of the sponge skeletons as examples for natural structural biocomposites are of fundamental scientific relevance. Recently, we show that some demosponges (Verongula gigantea, Aplysinasp.) and glass sponges (Farrea occa, Euplectella aspergillum) possess chitin as a component of their skeletons. The main practical approach we used for chitin isolation was based on alkali treatment of corresponding external layers of spicules sponge material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 52 publications
(62 reference statements)
1
40
0
Order By: Relevance
“…DNA-tagged gold nanoparticles can affect phosphorylation in relation to kinase activity that helps to inhibit the indirect effect of DNA functions and thus lysis of the insect-pest tissue leads to death of the S. litura. DNA-conjugatedgold nanoparticles have an effect on kinase activity (Brennan et al 2006;Wang et al 2006;Ehrlich et al 2008). In this context, DNA-tagged nanopolymer has a tremendous potential to locate the specific damaged part of the tissues in relation to its application in different physiological processes (Stadler et al 2007;Liedl et al 2010).…”
Section: Resultsmentioning
confidence: 99%
“…DNA-tagged gold nanoparticles can affect phosphorylation in relation to kinase activity that helps to inhibit the indirect effect of DNA functions and thus lysis of the insect-pest tissue leads to death of the S. litura. DNA-conjugatedgold nanoparticles have an effect on kinase activity (Brennan et al 2006;Wang et al 2006;Ehrlich et al 2008). In this context, DNA-tagged nanopolymer has a tremendous potential to locate the specific damaged part of the tissues in relation to its application in different physiological processes (Stadler et al 2007;Liedl et al 2010).…”
Section: Resultsmentioning
confidence: 99%
“…In a previous study, the silicatein protein has been demonstrated to exist within the silica layers of Monorhaphis chuni spicules (Müller et al 2008c). Subsequently, collagen has been proposed to be located on the surfaces of those lamellae (Ehrlich et al 2008). However, this conclusion must be substantiated in the future by protein analysis data from NaDodSO 4 -PAGE and also by direct chemical/molecular biological analyses or by immunochemical approaches (Ehrlich et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The link that may exist between polysaccharides and the formation of biosilica seems to be an interesting area to explore. We are aware of evidence that some diatoms produce extracellular chitin (a PCH precursor), and that there is no proof that chitin-like biomolecules are present inside diatom cells [9][10][11][12][13][14]. Therefore, the approach followed herein is an attempt to "model" silicic acid "pre-concentration" in vitro, just prior to its condensation yielding colloidal silica, or essentially to delay silicic acid condensation.…”
Section: Macromolecules That Affect Silicificationmentioning
confidence: 99%
“…The presence of chitin within the framework skeleton of Farrea occa [9] and Euplectella aspergillum [10] as well as separate spicules Rossella fibulata [11] could also be revealed by gentle NaOH-based desilicification technique established by Ehrlich et al [12,13]. It was suggested that silicate ions and silica oligomers preferentially interact with glycopyranose rings exposed at the chitin surface, presumably by polar and H-bonding interactions [14].…”
Section: Introductionmentioning
confidence: 99%